PROTECTION OF WOMEN FROM HARASSMENT AND VIOLENCE (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
The protection of women from harassment and violence is a pressing human rights concern that warrants urgent attention and concerted efforts from governments, civil society, and individuals across the globe. Gender-based violence, including harassment, rape, and domestic violence, is a pervasive and debilitating phenomenon that affects millions of women and girls worldwide. The alarming statistics and heart-wrenching stories of victims of harassment and violence underscore the gravity of this issue and the need for collective action to prevent, protect, and prosecute such crimes.